Pharmaceutical equivalence and stability of Furosemide tablets in Argentina - Brevedan, Marta Ingrid Victoria (2019)
Furosemide is a widely used diuretic, indicated in the treatment of hypertension and edema. This active pharmaceutical ingredient is classified as Class IV in the Biopharmaceutical Classification System. The World Health Organization recommends an oral dose of 40 mg. The aim of the present work was to evaluate and compare critical quality attributes, including in vitro dissolution characteristics, of eight furosemide tablet brands of Argentine market, and determine their pharmaceutical equivalence. Furthermore, this research aimed to evaluate the effect of storage (twelve months after natural aging conditions) over those critical properties. At time zero of analysis, all evaluated samples fulfilled specifications for friability, hardness, disintegration, assay, uniformity of dosage units and dissolution tests. After storage, all formulations fulfilled the assay and dissolution test specifications, with no statistical differences recorded for the obtained results. Comparison of dissolution profiles was also assessed in terms of the model independent parameter called dissolution efficiency. Highly significant differences were recorded between reference and four multisource formulations. The same differences were found at the beginning of the study (time zero) and after one year of storage. One product presented the lowest dissolution efficiency results, associated to highly significant differences when compared to the other formulations. However, the obtained results reveal that the evaluated samples complied with codified quality control tests, and consequently can be qualified as pharmaceutical equivalents. Natural aging conditions clearly not affected the stability of the evaluated products.